FAKTOR UMUR DAN PARITAS AKSEPTOR KB TERHADAP PEMILIHAN KONTRASEPSI SUNTIK - Lina Darmayanti Bainuan (Jurnal Kebidanan Akademi Kebidanan Griya Husada Surabaya, 2017)
Indonesia faces a problem with the rate of population growth in 2005-2015 of 1.49 percent per year. To overcome this, the government promotes Family Planning. The accuracy of clients in choosing contraception strongly supports the success of the Family Planning program. Contraceptive selection is influenced by several factors, namely age, parity, work, education, and so forth. In the village of Kendal Pecabean from year to year, there is the highest demand for injectable contraception. In 2016 there were 444 people interested in injection contraception (57.6%) exceeding the 2016 PPM of 30.28%. The purpose of this study was to determine the age and parity of family planning acceptors for the selection of injectable contraception. Method: This study used a descriptive method which became the population of all KB acceptors in Kendal Pecabean village in the period of January-June 2017 as many as 396 people, the sampling was done by Systematic Random Sampling with a sample size of 191 people. The research instrument was through secondary data by looking at the family data collection in Kendal Pecabean Village and then processed using frequency tabulation and cross tabulation. Results: The results of the study showed that the majority of acceptors aged 20-35 years were 98 people (51.31%) and the majority were primiparous, 123 people (64.40%), who chose injection contraception which was 107 people (56.02%). The results of cross tabulation of the majority of acceptors who chose injection contraception were 20-35 years old as many as 64 people (65.31%) and as many as 72 primiparas (58.54%). Discussion: The majority of injection contraceptive voters were aged 20-35 years. and primipara. Therefore, in order for prospective acceptors to choose contraception according to age and parity, cross-sector counseling, counseling and collaboration are needed to hold a KB safari.